Deguelin inhibits expression of IκBα protein in Raji and U937 cells - Chen Wei-hua; Chen Yan; Cui Guo-hui (Acta Pharmacologica Sinica; Vol 27, No 4 (April 2006): Acta Pharmacologica Sinica, 2016)
Aim: To determine whether deguelin can regulate the expression of nuclear factor kappa B (NF-κB) binding protein (IκBα) in U937 human leukemia cells and Raji human B lymphoma cells. Methods: The localization of IκBα protein was investigated by using an immunofluorescence method. The expression of IκBα and NF- κB /p65 proteins in Raji and U937 cells were investigated by using Western blotting. Apoptosis was detected through annexin V/PI double-labeled cytometry. Results: IκBα localized in the cytoplasm in untreated and deguelin-treated cells. After treatment with tumor necrosis factor α (TNF-α) or deguelin plus TNF-α for 15 min, there was a substantial reduction in the amount of IκBα protein. The expression of IκBα was downregulated by deguelin in Raji and U937 cells. Deguelin induced apoptosis in U937 cells. Conclusion: Deguelin inhibited the expression of IκBα protein in U937 and Raji cells. The anti-proliferative activity of deguelin is related to the signal pathway of NF-κB.